Modelos COM-Poisson correlacionados - Pereira, Glauber Márcio Silveira (Universidade Federal de São Carlos, 2019)
In this thesis two discrete distributions are proposed: Correlated COM-Poisson (CPC) and Generalized partially correlated COM-Poisson (CPGPC). We have also proposed regression models for the Generalized partially correlated Poisson distribution (PGPC) (proposed by Luceño (1995)). We calculated the probability mass function for all distributions with two parametrizations. The distributions were constructed using the same expansion made by Luceño (1995) in the construction of the correlated generalized Poisson distribution. The CPC Correlated COM-Poisson distribution is the same expansion of the zero-inflated COM-Poisson distribution ZICMP. For the CPGPC Generalized partially correlated COM-Poisson distribution, the characteristic function, probability-generating function, moments, and the maximum likelihood estimation for the two parametrizations were determined. We performed the probability mass function, quantile and random number generator of the distributions quoted in program R.
Correlated COM-Poisson Models
Keywords: Distribuição COM-Poisson; Distribuições com correlação; Distribuição Poisson generalizada parcialmente correlacionada; Modelos de regressão; COM-Poisson distribution; Correlated distributions; Generalized partially correlated Poisson distribution; Regression models; CIENCIAS EXATAS E DA TERRA::PROBABILIDADE E ESTATISTICA